2019
DOI: 10.1002/qj.3600
|View full text |Cite
|
Sign up to set email alerts
|

Trends in and closure of the atmospheric angular momentum budget in the 20th century in ERA‐20C

Abstract: It is well known that global warming in the 20th century has influenced the global circulation of the atmosphere. Atmospheric angular momentum (AAM), a measure of the rotation of the atmosphere around the Earth's axis, is a useful quantity to investigate changes in the global atmospheric circulation. In this study, 20th century trends in the AAM budget are determined using the ERA‐20C reanalysis data of the European Centre for Medium‐Range Weather Forecasts (ECMWF). In addition, the closure of the AAM budget i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…An earlier study by Paek and Huang (2012) compared five different reanalyses and found very different trends in the datasets. For the longer Twentieth Century Reanalysis (Compo et al 2006(Compo et al , 2011 there appears to be a positive trend especially in the ERA-20C reanalysis (Veerman and Heerwaarden 2019), but overall, the trends in reanalysis data are not yet consistent. By contrast, Paek and Huang (2012) find that interdecadal variations in global AAM are well reproduced in the reanalysis datasets.…”
Section: Sea Surface Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…An earlier study by Paek and Huang (2012) compared five different reanalyses and found very different trends in the datasets. For the longer Twentieth Century Reanalysis (Compo et al 2006(Compo et al , 2011 there appears to be a positive trend especially in the ERA-20C reanalysis (Veerman and Heerwaarden 2019), but overall, the trends in reanalysis data are not yet consistent. By contrast, Paek and Huang (2012) find that interdecadal variations in global AAM are well reproduced in the reanalysis datasets.…”
Section: Sea Surface Temperaturementioning
confidence: 99%
“…Atmospheric angular momentum (AAM) has been used to study changes in the global circulation on multiple time scales ranging from synoptic to millennial (Paek and Huang 2012;Veerman and Heerwaarden 2019). AAM is a measure of the rotation of the atmosphere about Earth's axis and is altered through exchanges with the solid Earth also rotating about its axis (Peixoto and Oort 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation